Teaching roles and communication strategies in interactive web broadcasts for practical lab and field work at a distance - Brown, Venetia; Collins, Trevor; Braithwaite, Nicholas St. John (Frontiers in Education, 2023)
Despite the widespread use of synchronous technologies in online and distance learning environments, it is still challenging for distance educators to use effective pedagogical strategies and ensure the best possible interaction for undergraduate students. Within science disciplines, teaching and learning are particularly challenging due to not being co-located with actual experimental equipment in laboratory or field settings. Compared to face-to-face practical work, socio-emotional challenges can exist in distance practical work. For instance, face-to-face settings make feedback, rapport and relationship-building more readily available whereas interaction and support may be hampered, delayed, or require frequent fostering in an online or distance learning environment. Several interactive learning environments can mitigate these challenges. For example, students and lecturers can converse in real-time using webcasting technologies as a way to observe practical work and enhance cognitive and affective engagement. Team-teaching and effective communication strategies can provide pedagogical and social synergy as well as increased student interaction and engagement.This study investigates the teaching roles and communication strategies teaching teams used in interactive web broadcasts across five undergraduate practical science and technology modules at a distance-learning university. Using a qualitative approach, the study used interaction analysis methods to analyse fourteen web broadcast transcripts and text-chat logs. Focus groups, semistructured interviews and questionnaire data from the teaching teams and students were conducted to gain a fuller picture of experiences using and engaging with web broadcasts. Results show that affective communication strategies predominated the web broadcasts although the most frequent was a cognitive strategy. The use of these strategies varied depending on the role that the teaching team occupied during the web broadcasts. Triangulation, which was applied to confirm the results from various methods, showed that the strategies used satisfied the interests and expectations of the students. The results are applicable to other distance and conventional campus-based institutions that offer courses in practical science and technology as well as those that deliver courses via synchronous delivery methods with a focus on student engagement and practical work.